Generalization of the Prokhorov multidimensional analog of the Chebyshev inequality - Sokolov, N. V.; Соколов, Н. В.; Соколов, Н. В. (Institute of Mathematics, NAS of Ukraine, 2006)
We prove two theorems on upper and lower bounds for probabilities in the multidimensional case. We generalize and improve the Prokhorov multidimensional analog of the Chebyshev inequality and establish a multidimensional analog of the generalized Kolmogorov probability estimate.